2003
DOI: 10.1046/j.1464-410x.2003.04310.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in benign prostatic hyperplasia‐specific quality of life with dutasteride, the novel dual 5α‐reductase inhibitor

Abstract: £ 15 mL/s. BII scores were recorded at baseline and each study visit. Clinically and statistically significant changes in BII scores from baseline were investigated for each study visit. Logistical regression analysis was used to assess the significance of baseline prostate volume, symptoms, BII item 3, baseline Q max , serum dihydrotestosterone, testosterone, PSA, age and weight in predicting the BII score at 2 years. RESULTSDutasteride, but not placebo, resulted in clinically and statistically significant im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 30 publications
2
30
1
Order By: Relevance
“…Consistent improvements in QOL measures were also seen in a study by O'Leary et al, 17 who previously assessed the effect of dutasteride on QOL using the BPH impact index questionnaire in patients randomized to treatment with dutasteride or placebo. The BPH impact index is a validated questionnaire 12 that measures the impact of symptoms that may affect a patient's health status and which serves as a practical approach to deciding whether medical or surgical intervention is necessary.…”
Section: Discussionsupporting
confidence: 68%
“…Consistent improvements in QOL measures were also seen in a study by O'Leary et al, 17 who previously assessed the effect of dutasteride on QOL using the BPH impact index questionnaire in patients randomized to treatment with dutasteride or placebo. The BPH impact index is a validated questionnaire 12 that measures the impact of symptoms that may affect a patient's health status and which serves as a practical approach to deciding whether medical or surgical intervention is necessary.…”
Section: Discussionsupporting
confidence: 68%
“…23 Investigations on QOL in men with LUTS have been almost limited to benign prostatic hyperplasia. Analyses using the Short Form-36 and other generic QOL questionnaires 24 or disease-specific instruments have uniformly shown that LUTS, storage symptoms in particular, have negative effects on QOL, 25 and that medical therapy 26 and surgical interventions 27 improve the lowered QOL. Few investigations have looked into the relationship between LUTS and QOL.…”
Section: Epidemiology and Qolmentioning
confidence: 99%
“…Each of seven symptoms (frequency, urgency, weak stream, intermittency, incomplete emptying, straining to urinate, and nocturia) are scored by the patient on a 0-5 scale based on their frequency. A score of less than 7 indicates mild symptoms; a score of [8][9][10][11][12][13][14][15][16][17][18][19] indicates moderate symptoms, and a score of greater than 19 indicates severe symptoms. In addition to symptoms that may have a negative impact on the quality of life, BPH/BPE can result in acute urinary retention, Dovepress recurrent urinary tract infections (UTI), bladder stones, urinary incontinence, gross hematuria and renal failure.…”
Section: Introductionmentioning
confidence: 99%